Effect of Storage Temperatures on the Moisture Migration and Microstructure of Beef. (21st June 2018) - Li, Xia; Wang, Hang; Mehmood, Waris; Qian, Shuyi; Sun, Zhen; Zhang, Chunhui; Blecker, Christophe
Abstract : The effects of freezing temperature on the microstructure and moisture migration of beef were investigated, aiming to provide the potential theoretical basis for the beef storage. Drip loss, surface hydrophobicity, and secondary structure of myofibrillar proteins, ice crystal, and micro- and ultrastructure of meat were analyzed at 4°C, −1°C, −6°C, −9°C, −12°C, and −18°C, respectively. Results indicated that the drip loss and surface hydrophobicity of samples stored at −12°C were significantly lower than that stored at 4°C and −1°C (p < 0.05 ) and no significant difference with −18°C (p > 0.05 ). Result from Fourier transform infrared spectroscopy suggested that protein denaturation occurred after storage. There was an increase in α -helices and decline in random coil at lower temperature (−12°C and −18°C). It was indicated that the samples stored at −12°C and −18°C could effectively restrain the denaturation of protein and maintain the stability of secondary structure. The analysis of the ice crystal and micro- and ultrastructure of the muscle indicated that the structure of samples stored at −12°C and −18°C had more integrity and was complete than that stored at 4°C and −1°C. The spaces (water "reservoir" and "channel") where was the origination of drip were small. Furthermore, the results of low-field nuclear magnetic resonance and 1 H magnetic relaxation image showed that the freezing at −12°C could inhibit the migration of immobilized water to free water.